(untitled) (Fiep Bulletin - online, 2013)
Researchers and educators have shown a growing interest in the study of the relationships between families and schools because of its importance to education and human development. In this theoretical paper, we present some reflections on family involvement with the school and its impact on learning and student development. The benefits of a good integration and the implications of a lack of integration between the two contexts are discussed briefly, and are described aspects of the relations established between them, which have been focused on empirical research. Special attention is given to the concepts and types of family-school involvement and perceptions of parents and teachers about this involvement. Finally, we emphasize the need for a more effective integration between the family and the school, respecting the peculiarities of each segment, and the implementation of research that take into account the interrelationships between the two context.